The Promising Role of Mushrooms as a Therapeutic Adjuvant of Conventional Cancer Therapies - Ana Isabel Plácido; Fátima Roque; Manuel Morgado (Biologics, 2022)
Complementary and alternative medicine (CAM) has been fronted as an alternative due to its potential for holistic treatment. Many CAMs are plant-derived, including algae and mushrooms that have been used widely in many parts of the world, where they are regarded as biological response modifiers. The purpose of this article was to review the role of mushrooms as an adjuvant in conventional therapies, to reveal the therapeutic substances of mushrooms as an adjuvant in conventional therapies, to bring together the available scientific data on the medical effects of mushrooms in oncology, and verify its efficacy and safety. A literature search was conducted in September 2021 on the MEDLINE-PubMed and Cochrane databases to identify relevant randomized controlled trials or clinical trials studies addressing the use of whole mushroom formulations as complementary therapy during conventional cancer treatment.: The findings from the present study suggest that mushrooms may act as a potentiator of host defense mechanisms and decrease adverse events for patients with cancer undergoing conventional therapies. New protocols to conduct clinical trials are needed to elucidate the possible active mechanisms and clinical benefits of these fungi in various types of cancer.